USE OF SELF-COMPACTING CONCRETE DURING RECONSTRUCTION OF THE BUILDING FOR THE ADMINISTRATION SERVICE CENTRE - Bugayevskyi, S.; Voronova, Ye.; Shtefan, O.; Бугаевский, С. А.; Воронова, Е. М.; Штефан, О. Н.; Бугаєвський, С. О.; Воронова, Е. М.; Штефан, О. М. (Харьковский национальный автомобильно-дорожный университет, 2016)
Twophase introduction of superplasticizer additive influence on the properties of concrete mixture was researched. The obtained results allowed concreting of strengthening for the columns building. Herewith, 40 % of SP additive together with 12 % of mixing water were introduced directly into the concrete mixer truck at the moment of its arrival to the construction site, with subsequent agitation of concrete mixture.
ПРИМЕНЕНИЕ САМОУПЛОТНЯЮЩЕГОСЯ БЕТОНА ПРИ РЕКОНСТРУКЦИИ ЗДАНИЯ ПОД ЦЕНТР ПРЕДОСТАВЛЕНИЯ АДМИНИСТРАТИВНЫХ УСЛУГ
ЗАСТОСУВАННЯ САМОУЩІЛЬНЮВАНОГО БЕТОНУ ПІД ЧАС РЕКОНСТРУКЦІЇ БУДІВЛІ ПІД ЦЕНТР НАДАННЯ АДМІНІСТРАТИВНИХ ПОСЛУГ
Keywords: self-compacting concrete mixture; flow of cone; obstacle crossing ability; time of flowing through a V-shaped funnel; concrete mixer trucks (mixers); columns; building; суперпластификатор; самоуплотняющийся бетон; бетонная смесь; расплыв конуса; автобетоносмеситель; суперпластифікатор; самоущільнюваний бетон; бетонна суміш; розплив конуса; автобетонозмішувач; 666.97